TRANSFORMASI PENDIDIKAN ISLAM DALAM MENCETAK GENERASI RABBANI DI ERA DIGITAL - Sarima, Andi - (JURNAL AL-QAYYIMAH, 2023)
This study discusses the transformation of Islamic education in producing rabbani generations in the digital era. There are three main objectives achieved in this research, namely first, to explain the urgency of transforming technology-based Islamic education; second, expressing the challenges of Islamic education in producing rabbani generations in the digital era; third, offering an efficient learning model in printing the rabbani generation in the digital era. In achieving these objectives, researchers used qualitative methods with a library research approach. The results of this study explain that the urgency of transforming Islamic education aims to help people learn and understand Islamic beliefs. This is done in an effort to develop strong morals, religious knowledge and piety, as well as the ability to live up to Islamic principles. Islamic education also plays an important role in strengthening individual and societal Islamic identity. Therefore, the challenge for Islamic education in producing the rabbani generation in the digital era is that there is no adequate access to technological infrastructure in some areas which will limit the availability of Islamic teaching through digital platforms. A person's capacity to use digital technology in Islamic education can also be affected by economic inequality. In addition, the learning models applied are project-based learning models, problem-solving based learning models, distance learning models, game-based learning models, collaborative learning models, video- and animation-based learning models.